A patent review of apelin receptor (APJR) modulators (2014-2019). (2nd April 2020) - Fischer, Conrad
ABSTRACT: Introduction : The apelinergic system is regarded as a novel therapeutic target for cardiovascular health, fluid homeostasis, the hypothalamic-pituitary-adrenal (HPA) axis as well as carbohydrate and fat metabolism. Two endogenous peptide ligands, namely apelin and elabela, have been demonstrated to moderate its various metabolic and neurological functions. Both bind with high (sub)-nanomolar affinity to APJR but get degraded rapidly in circulation. In addition, various diseases have been associated with the depletion of these regulatory peptides. Besides blocking the degrading proteases, a common strategy in targeting drugs to APJR is the development of metabolically stable peptide analogs or small molecule modulators. Supporting this trend, patent literature has evolved from 121 patents in 2014 to a total of almost 1000 patents today. Areas covered : This review includes WIPO-listed small molecule and peptide-based agonists, antagonists and allosteric modulators of APJR published between 2014 and 2019. Expert opinion : Both apelin peptide analogues and small molecule modulators are emerging, only recently including one example of an elabela-based analogue. Patent activity is predominantly on agonistic modulators since they show higher affinity and fewer off-target effects. Although several low nanomolar binders with half-lives exceeding 24 h have been confirmed in animal models, clinical validation of these drug-targets is sparse.